2010
DOI: 10.1007/s11630-010-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance and flow condition of small-sized axial fan and adoption of contra-rotating rotors

Abstract: Small-sized axial fans are used as air coolers for electric equipments. But there is a strong demand for higher power of fans according to the increase of quantity of heat from electric devices. Therefore, higher rotational speed design is conducted, although it causes the deterioration of the efficiency and the increase of noise. Then the adoption of contra-rotating rotors for the small-sized axial fan is proposed for the improvement of the performance. In the present paper, the performance and the internal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 5 publications
0
18
0
3
Order By: Relevance
“…The first counter-rotating machines have appeared in aeronautic and marine applications, in open configuration. Nowadays, these machines with two coaxial axial-flow fans that rotate in opposite direction see a revival of interest in several distinct configurations -open and ducted flows, shrouded or not shrouded rotors-in various subsonic regime applications [7][8][9] . The previous studies concluded that the presence of the rear rotor improves the global efficiency 3,4 and also increases the operating flow-rate range.…”
Section: Introductionmentioning
confidence: 99%
“…The first counter-rotating machines have appeared in aeronautic and marine applications, in open configuration. Nowadays, these machines with two coaxial axial-flow fans that rotate in opposite direction see a revival of interest in several distinct configurations -open and ducted flows, shrouded or not shrouded rotors-in various subsonic regime applications [7][8][9] . The previous studies concluded that the presence of the rear rotor improves the global efficiency 3,4 and also increases the operating flow-rate range.…”
Section: Introductionmentioning
confidence: 99%
“…The counter-rotating impellers driven separately by the isolated motors have been presented by Prof. Shigemitsu et al [6] [7], but the proposed impellers quite differ from them as the impellers are driven, in the smart control, by the peculiar motor with the double rotational armatures. This paper investigates experimentally the effects of the impeller profiles not only the pump performances but also on the rotational speeds of the front and the rear impellers against the discharge, using the four kinds of the impellers whose loads are low and/or high at the normal discharge.…”
Section: Front Impellermentioning
confidence: 99%
“…Le dĂ©veloppement de machines Ă  forte vitesse spĂ©cifique et de taille rĂ©duite en rĂ©gime subsonique suscite actuellement une forte demande dans de nombreux domaines industriels [Shigemitsu et al, 2007;Shigemitsu et al, 2010;Pin et al, 2011]. Des machines conventionnelles amènent un rendement bas et gĂ©nèrent un bruit aĂ©rodynamique relativement Ă©levĂ©: problème crucial pour des raisons de confort de l'utilisateur (ventilateurs d'ordinateurs) ou de discrĂ©tion acoustique (circulateurs de sous-marins).…”
Section: Introductionunclassified